Nikki'R. Keddie, An Islamic Response to Imperialism; Political and Religious Writings of Sayyid Jamal ad Dinal Afghani, Berkeley, University of California Press, 1983, 212 pp. - Cisneros, Fernando (Estudios de Asia y África, 1984)
-